2001
DOI: 10.1097/00001756-200102120-00023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propofol on NMDA- or nitric oxide-mediated neurotoxicity in vitro

Abstract: Acute brain ischemia causes neurotoxic cascades including NMDA receptors and NO. Propofol, an i.v. anesthetic, is thought to have a neuroprotective effect. We investigated the influence of propofol on NMDA/NO neurotoxicity using Shibuta's established model of primary brain cultures. Cortical neurons prepared from E16 were used after 13-14 days in culture. The neurons were exposed to various concentrations of propofol with NMDA or NO-donor. The survival rates of neurons exposed to 30 microM NMDA with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Primary cortical cultures were prepared as described previously (Shibuta et al, 1998, 2000, 2001). Rat fetuses at embryonic day 16 were removed surgically from anesthetized pregnant Wistar rats (obtained from Nihon SLC Hamamatus Japan), and their brains were isolated under the microscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary cortical cultures were prepared as described previously (Shibuta et al, 1998, 2000, 2001). Rat fetuses at embryonic day 16 were removed surgically from anesthetized pregnant Wistar rats (obtained from Nihon SLC Hamamatus Japan), and their brains were isolated under the microscope.…”
Section: Methodsmentioning
confidence: 99%
“…We used Shibuta's model (Shibuta et al, 1998, 2000, 2001) to evaluate cytotoxicity. Three or four photomicrographs were made of each well shortly before exposing the cells to hypoxia and at the end of the experiment according to the grid arrangement of the dish.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism involved in the neuroprotective effect of ketamine has been poorly determined. Ketamine exhibits anesthetic effects by inhibiting NMDA receptors in the central nervous system, where they are widely expressed [24,25]. In this study, NMDA receptor expression was also detected in BV2 cells (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…[1] The Diprifusor ® system, the first commercial TCI device used worldwide, displays effect-site concentration of propofol (Cep) as well as plasma concentration calculated according to the Marsh model, which is one of the most frequently used pharmacokinetic models for propofol. [2] However, the Marsh model does not adjust for age and weight is the only model covariate.…”
Section: Introductionmentioning
confidence: 99%